2014
DOI: 10.1111/lre.12069
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentation and internal phosphorus loads in Krishnagiri Reservoir, India

Abstract: This study examines sedimentation rate and its consequences on the bathymetry, capacity and internal phosphorus loading of Krishnagiri Reservoir in Tamil Nadu, South India, utilizing an acoustic Doppler profiler and remote sensing data in an ArcGIS environment. There was a significant change in the reservoir bathymetry for the year 2012, compared with the 2007. The sedimentation rate was 0.818 MCM from 1960 to 1990 and 0.83 MCM over past 5 years. The present reservoir volume is 35.57 MCM, having been reduced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The higher total phosphorus concentrations measured during the NEM and SWM seasons indicated an increased total phosphorus input from the catchment inflows. Krishnagiri Reservoir's internal phosphorus loading rate is relatively high and directly proportional to its anoxic area (Arunbabu et al, 2014). The total phosphorus concentrations were higher near the structure and middle of the reservoir surface area (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The higher total phosphorus concentrations measured during the NEM and SWM seasons indicated an increased total phosphorus input from the catchment inflows. Krishnagiri Reservoir's internal phosphorus loading rate is relatively high and directly proportional to its anoxic area (Arunbabu et al, 2014). The total phosphorus concentrations were higher near the structure and middle of the reservoir surface area (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The Ponnaiyar River drains this medium‐sized storage structure that serves multiple purposes ranging from irrigation to fish culture. Previous studies by Arunbabu et al (2014) indicated the internal phosphorus loading rate was relatively high, being directly proportional to its anoxic area that led to eutrophication of the reservoir. This eutrophication is supported by the fact that the tilapia o massambius species of fish, which strives in water containing high nutrient concentrations are present in great numbers in this reservoir.…”
Section: Study Areamentioning
confidence: 95%
See 1 more Smart Citation
“…; Arunbabu et al . ). Analysis of measured sediment data in and out of the TGR indicated that sedimentation within the TGR is far less than that projected by numerical models utilized prior to when the dam was built.…”
Section: Discussionmentioning
confidence: 97%
“…Sediment transport obviously controls a reservoir's lifespan (Tarela & Men endez 1999;Morris et al 2006;Zeleke et al 2013;Arunbabu et al 2014). Analysis of measured sediment data in and out of the TGR indicated that sedimentation within the TGR is far less than that projected by numerical models utilized prior to when the dam was built.…”
Section: Discussionmentioning
confidence: 99%